Educação em saúde para A Pastoral da Criança abordagem Freireana - Souza, Francisco Ivan de (2003)
The Children's Pastoral, a mission carried out by the Roman Catholic Apostolic Church, is present ali over the country. It's present in Brazilian communities, searching to rescue the quality of life in ali circumstances. Thus we have marked out for our studies the following objectives; analyze the way the planning of the actions of the Children's Pastoral of Fortaleza's archdiocese occur from the point of the theoretical-practical perspectives; study how the educational practices in the health area in the Children's Pastoralof Fortaleza's archdiocese are developed; to build up collective strategies that can provide the Health Education practice in the developed actions in the Children's Pastoral of Fortaleza's archdiocese, using a planning which is always present. This research was developed under a qualitative approach, using Paulo Freire's methodology of the "Circulo de Cultura" - Culture Circle. We used Fortaleza's Cathedral as a place for our meetings from April-2002 to January-2003, with the 10 coordinators of the Children's Pastoral who voluntarily participated in this research. The data was collected through the "Circulo de Cultura" which favored us with generating words. The results were examined, using Bardin's analyzing contents, making use of thematic analysis procedures. From that point on we verified that the Children's Pastoral occurs because of the leaders' self-denial and efforts; the volunteer work has helped a lot in the families' health orientation; the Pastoral invests in the human improvement; the Pastoral performs Health Education actions. In synthesis, we can assert that the Children's Pastoral aims at binding together the living forces as the representatives from inhabitant associations, from churches, from cultural movements, mothers' groups, parents' associations, and others. Then, we conclude that, as the health promotion is an action which enables the community to take part in people's life quality improvement, causing a physical, mental and social welfare, according to the Ottawa letter (1986), Children's Pastoral planning should consider the fact that the Health educative practices still occur in a dominated-dominant relation, that means that it's a supervised participation. The woman's presence in the Children's Pastoral deserves a great emphasis: 90% of the participants of the pastoral are women, that is . ' why, the Children's Pastoral must give priority and develop Health Education practices which are related to women's health, such as: the equality on the job vii organization rights, some support not only during the deliveries but also during their maternity leave and during the period may necessary for taking care of their sick children. With regard to the participative planning in the Health Education practices in the Children's Pastoral, 80% of the agents that the idea would be interesting, 20% said it would not. The ones who said yes just showed their opinions, that we can not improvise health actions, and the ones who said no, explained that the bureaucracy is very severe and there are not many changes. So, the point is, that it's not only planning, but also the way it's planned. The way things are planned determines the quality of health education actions. Neither rnethodoloqy is good enough for health improvement, because planning is not a panacea, but an action instrument that helps other actions in the systematic and organized accomplishment of some activities as a social practice. So, in the health improvement, the educational process is not an end, but a compromise which starts at each action and reflection and the initiative that makes us risk ourselves to produce the improvement of the life quality.